KAJIAN WUJUD INTERIOR TERHADAP AKTIVITAS PENYANDANG TUNA NETRA DI BALI: KAJIAN WUJUD INTERIOR TERHADAP AKTIVITAS PENYANDANG TUNA NETRA DI BALI - I Nyoman Yoga Trisna Putra (Universitas Telkom, 2025)
Abstract: Blindness is a general term used to describe a condition in which a person experiences impairment or limitations in their sense of sight. This gives rise to special needs—including physiological, personal, and social aspects—for people with visual impairments. Government efforts to address the issues faced by the visually impaired include social rehabilitation, empowerment, and social security and protection, one of which is carried out through the Bali chapter of the Indonesian Association of the Visually Impaired (PERTUNI). This organization strives to develop orientation and mobility skills as well as the strengths possessed by people with visual impairments, one of which is by conducting artistic activities that involve people with visual impairments as the primary participants and visitors with normal vision as supporting participants. The objective of this study is to examine interior design based on the needs of the visually impaired, identify the factors that make it difficult for the visually impaired to navigate spaces, and establish criteria for interior design that can meet their needs, thereby enhancing their orientation and mobility and providing a sense of comfort and safety during all types of activities. The process of examining interior design employs a qualitative approach, beginning with the collection of data on the existing interior of the PERTUNI Bali building as a case study. Based on the research findings, the factors that make it difficult for visually impaired individuals to identify their surroundings and cause them to become disoriented within building interiors include inconsistencies in spatial planning, spatial elements, complementary spatial elements, and spatial facilities in relation to the primary users of the building’s interior—namely, visually impaired individuals. Keywords: Form, Interior, Activity, Visually Impaired